2021
DOI: 10.1007/s43477-020-00003-y
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of a Training Team-Coordinated Approach to Implementation

Abstract: It is now widely understood that successful implementation of evidence-based treatments is facilitated by several favorable conditions (e.g., community buy-in, invested agency leadership). However, strategies for supporting agencies in promoting these conditions have been examined to a lesser extent. In this exploratory study, the implementation support procedures of Parenting with Love and Limits (PLL), an evidence-informed family treatment for child/adolescent behavior problems in which the training team fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Each of the three Pre-Implementation stages are positively, significantly, and independently associated with program start-up. Although the Pre-Implementation phase (across all of the first three stages) typically stands alone (e.g., [ 16 , 21 ]) and was shown in the current study to be predictive of program start-up, the relative importance of each stage was remarkable. This provides further evidence that each of the three stages measures different aspects of Pre-Implementation fidelity [ 25 ].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Each of the three Pre-Implementation stages are positively, significantly, and independently associated with program start-up. Although the Pre-Implementation phase (across all of the first three stages) typically stands alone (e.g., [ 16 , 21 ]) and was shown in the current study to be predictive of program start-up, the relative importance of each stage was remarkable. This provides further evidence that each of the three stages measures different aspects of Pre-Implementation fidelity [ 25 ].…”
Section: Discussionmentioning
confidence: 58%
“…This is supported by multiple studies, which have found that sites with higher implementation process fidelity early-on were more likely to make it to the point of delivering services to clients [ 12 15 ]. Additionally, in a descriptive study of 23 implementation attempts [ 16 ], sites that eventually became competent in delivering the intervention program were those that—early-on—had 100% implementation process fidelity. In contrast, of sites that did not reach competency in program delivery, the average level of implementation process fidelity during Pre-Implementation was only 47%.…”
Section: Introductionmentioning
confidence: 99%
“…A third Final Stage score indicates the final stage achieved in the implementation process (Stages 1-8). The SIC has been adapted or customized for multiple evidence-based practices (EBPs) [70][71][72][73][74][75] and evaluated across different system settings [51,76,77].…”
Section: Stages Of Implementation Completion (Sic) and The Resources ...mentioning
confidence: 99%
“…The SIC has been adapted or customized for multiple EBPs, through a clearly defined adaptation process ( Dubowitz et al, 2020 ; Nadeem et al, 2018 ; Saldana et al, 2012 , 2020 ; Sterrett-Hong et al, 2021 ; Watson et al, 2020 ). Several applications of the SIC have or are being evaluated in system settings focused on improving child or youth services ( Aalsma et al, 2019 ; Brown et al, 2014 ; Palinkas et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%